Dutch Therapists’ Professional Autonomy and Moral Agency After the Marketization and Bureaucratization of Mental Healthcare: Between Impracticalities and Impossibilities - Krikken Mulders, Linda; Tonkens, Evelien; Trappenburg, Margo (Professions and professionalism, 2024)
Over the last decades, western mental healthcare has increasingly been governed by market and bureaucratic principles. As a consequence, therapists are faced with conflicting demands and decreased autonomy. This study examines how they cope and whether their strategies suffice. Drawing on the direct experience of therapists through interviews, we demonstrate that psychologists have become quite skilled at balancing and navigating bureaucratic and market demands that were at odds with professionalism. However, when they were structurally faced with bureaucratic and market demands that were already irreconcilable with each other, these skills fell short. Trying to meet all requirements took up so much of their resources that sometimes, professional reasoning and agency disappeared altogether. In some cases, this led to detachment, burnout, and patient neglect. Our findings suggest that the public interest in having a well-functioning mental healthcare system requires more room for professional autonomy.